Patristic and Scriptural Arguments in St. Gregory Palamas on the Nature of Grace - Petrov, George Daniel; Mohor Obreja, Bogdan (Technium Social Sciences Journal, 2023)
Grace, according to the Orthodox definition, can be summarized as “the uncreated divine energy poured out by the Holy Spirit upon us through the risen and ascended humanity of Jesus Christ.” Thus, grace represents living communion with Christ in the Holy Spirit, which is why the Orthodox Church does not see grace as a good that can be separated from God.